Positioning Control Of Ball Screw System Driven By DC Motor - Chong, Shin Horng; Ting, Tze Ter; Sakthi Velu, Vasanthan (Trans Tech Publications, 2015)
This paper presents the comparison of positioning control between conventional PID controller and fuzzy PID controller. The controllers are applying into the ball screw system driven by DC motor to observe and analyze the change of the positioning output responses. The DC motor is used because it is easy to setup and control, has precise rotation and most importantly is low cost. As for ball screw mechanism itself, has smooth motion, not easy to wear out and high mechanical efficiency. The problem is arise when the used of conventional PID controller in the ball screw system driven by DC motor shows less adaptability to the changes of system parameter. Therefore, the objective of this project is to design an adaptive fuzzy PID controller to overcome the limitation of conventional PID controller. The performances between the conventional PID controller and fuzzy PID controller will be compared in order to validate the robustness of the fuzzy PID controller. So this project is to compare the robustness of two proposed controllers by comparing the results of ball screw table position when the parameter mass of load is set to vary. The experiment is started with designing the algorithms of fuzzy PID control and conventional PID controller, then the designed algorithm is applied onto the experimental that has been setup. The performances especially the transient response and steady state error between the controllers will be collected and compared by conducting the point to point positioning, tracking and variation of load weight experiments.